The Implementation of Learning Administration Supervision Can Improve Teacher Professionalism at Mts Nurul Huda for the 2019/2020 Academic Year : Pelaksanaan Supervisi Administrasi Pembelajaran Dapat Meningkatkan Profesionalisme Guru Mts Nurul Huda Tahun Pelajaran 2019/2020 - suhaibar suhaibar (Journal of Vocational Education and Information Technology (JVEIT), 2022)
This research is an Oversight Action Research (PTKp). Related to the social studies learning process, the author has carried out the social studies learning process with the material "Improving student learning outcomes by using a project work learning model in social studies subjects in grade IV SD Negeri 13 Koto Besar." Learning Social Sciences on the material of Natural Events and Their Influence on Social Life using the project work method can provide students' excitement in learning and avoid the monotonous teaching and learning processKeywords: Improving Student Learning Outcomes, Materials for Photosynthesis in Green Plants, Model